Local operators in krylov subspaces. (December 2019) - Huhtanen, M.
Abstract : For a bounded linear operator A on a Hilbert space H we study local spectral sets and their relation to the spectrum of the local operator. By the local operator we mean A restricted to a Krylov subspace [image omitted]  for a generic b ↦ H. Moreover we investigate the relation between σ(A), the spectrum of A, and the spectrum of the local operators are being studied.